Proposal to Enhance Fund Support for Low-Income Countries Hit by Public Health Disasters. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
The Fund's existing facilities for low-income countries (LICs) provide a vehicle for the speedy provision of financial assistance to member countries hit by natural disasters, either through the Rapid Credit Facility (RCF) or through augmentation of the funding already being provided through other facilities such as the Standby or Extended Credit Facilities. The quick disbursement of funds strengthens national financial capacity, including external payments capacity, to tackle relief and recovery challenges. To address catastrophic disasters, the Fund created a mechanism in 2010 to provide additional relief to its poorest and most vulnerable member countries to help meet their exceptional balance of payments needs. Under this mechanism, the Fund can provide grants from a trust fund-the Post Catastrophe Debt Relief (PCDR) trust-that are used to pay off debt service falling due to the Fund. These grants ease pressures on the member's balance of payments and create financial space by reducing its debt service burden. This paper proposes reforms to this mechanism to cover situations where the member is experiencing an epidemic of an infectious disease that constitutes a significant threat to lives, economic activity, and international commerce across countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet